Odor-Free Lyophilized Trout (Oncorhynchus mykiss) Powder in Gluten-Free Pasta: Nutritional, Techno-Functional, Sensory and Digestibility Evaluation - Emir Çoban, Özlem; Gül, Hülya; Eroğlu, Mücahit; Okutan, Tuba; Kilinçer, İlhan Firat; Çağiran Yilmaz, Feray (Mdpi, 2026)
Gluten-free (GF) products developed for individuals with celiac disease and gluten sensitivity often suffer from low protein and mineral content. Fish proteins offer a promising solution to address these deficiencies; however, the characteristic fishy odor and related technological challenges limit consumer acceptance. This study aimed to develop an innovative GF pasta with improved nutritional density and acceptable sensory quality by incorporating deodorized and lyophilized trout powder. GF pasta formulations were prepared using buckwheat flour, xanthan gum, and 5% or 10% odorless trout powder. Vinegar pretreatment was applied to reduce fish odor, while lyophilization was chosen to minimize nutrient losses. The samples were analyzed for nutritional composition, techno-functional properties, in vitro digestibility, and sensory attributes. Results showed that trout powder significantly increased protein and ash content compared to the control (p < 0.05). A slight darkening was observed in color analysis due to fish pigments and buckwheat phenolics, but overall visual stability remained high. In vitro digestibility revealed enhanced protein digestibility (p < 0.05) and a slight reduction in starch digestibility. Sensory evaluation demonstrated that odor scores (8) at 10% trout inclusion remained close to the control, reversing the commonly reported decline in acceptance with increasing fish content. These findings indicate that combining vinegar pretreatment with lyophilization enables the incorporation of fish proteins into GF pasta without sensory disadvantages, while simultaneously improving nutritional quality.
Keywords: gluten-free pasta; trout powder; deodorization with vinegar; lyophilization; buckwheat flour; sensory acceptance